Profitability of major private sector companies involved in the private finance initiative scheme - Ismail, Suhaiza (Universiti Utara Malaysia (UUM), 2011)
Private Finance Initiative (PFI) has become a widely used mechanism for delivering public services in the United Kingdom. Despite the extensive use of the PFI scheme and strong support from the private sector companies, it has often been controversial. One of the controversies is based on the claim that the private sector companies are making excessive profi ts from PFI projects. Hence, this paper aims at evaluating the profitability of several private sector companies which are heavily involved in the PFI projects. The analysis of the performance of private sector companies suggested that no clear evidence of excessive profi ts were made by the companies from their PFI involvement.